An analysis on nature of limited liability partnerships in Malaysia - Abdul Rahman, Hamizah; Mohd. Zain, Nor Razinah; Abd Ghadas, Zuhairah Ariff; Tengku Zainal Mulok, Tengku Adida; Othman, Nurul Syahira; Othman, Ghazali; Hassan, Muhammad Syafiq; Nadarajan, Ravindran (UiTM, 2021)
Limited Liability Partnership (LLP) is an additional form of business entity available for an entrepreneur who decides to carry on a business in Malaysia. The Companies Commission of Malaysia introduces this business entity under the Limited Liability Partnership Act (LLPA) in 2012. This paper looks into the history of the legislation of LLPA in Malaysia while using the doctrinal approach in analyzing the nature of LLP. The conceptual understanding of LLP and a valid definition of LLP is presented by referring to provisions of LLPA. Evaluation of the best features of LLP is provided, and the important provisions of LLPA are included and discussed in detail. This paper also reviews the relevant authorities and their responsibilities in monitoring LLP in Malaysia. By doing so, a clear exposure in the application of LLP can be provided. Finally, a recommendation for future research and a conclusion are provided at the end of the paper.